DEVELOPING READING MATERIAL BASED ON ISLAMIC VALUES FOR ENGLISH TEACHING DEPARTMENT OF STAIN MANDAILING NATAL - Sahyoni .; Lia Agustina Damanik; Syamsiah Depalina Siregar (Jurnal Education and Development, 2021)
Reading material that is contextually and academically appropriate for students' needs is an important component of teaching English. In reality, some of the reading material used by the lecturer is inadequate for the needs of the students. This research developed reading material that contextually applies to Islamic colleges and is appropriately suitable for students’ knowledge. To achieve the aims, the research design was a research and development (R and D). The respondents of the research were 52 students of the English Teaching Department STAIN Mandailing Natal. They were chosen to use a technique called purposive random sampling. As part of the research procedures, it carried out five phases: (1) conducting a need analysis with the student, (2) designing reading material based on Islamic values, (3) developing reading material based on Islamic values. (4) obtaining expert opinions on the validity of reading material (5) determining the feasibility of reading material. The research findings show students need reading material that covers: Islamic context in their reading materials since they study in Islamic-based campuses and stay in most Islamic-society regions. Then, students need reading material that is suitable for students’ knowledge level for text, illustration, pictures, even the example of reading material. The students also need an Islamic vocabulary in reading material, which may use them to apply in daily life. Expert validated this model of reading material and it yielded as valid and practical to be applied in reading subject specifically for English Teaching Department students of STAIN Mandailing Natal. After conducting dissemination to students for the practicality, this reading material is practical and applicable to be used for reading subjects. We can state that this reading material applies to lecturers and matches students’ needs appropriately.